Animals and nature in Philip Larkin’s “Going, Going,” and “Take One Home for the Kiddies” - Neupane, Rabindra (Ganeshman Darpan, 2024)
This article has focused on investigating the ecological awareness of Philip Larkin’s poems “Going, Going,” and “Take One Home for the Kiddies”. The poet problematizes animals and the natural world, yet the concerns of (non)humans have largely been one-dimensional and universal. This article examines Larkin’s poetry with a focus on his foresight of an impending catastrophe that environmentalists and ecocritics subsequently came to refer to as “the ecological crisis.” It examines two of Larkin’s poems, “Going, Going” and “Take One Home for the Kiddies” primarily concerning animal abuse and the environment. The link between Man and Nature is ultimately undermined by Larkin’s ideas regarding human manipulation of nature. By concentrating on these two poems by Larkin, the broader use of rhetorical elements demonstrates the poet’s sensitivity and outlines a precarious alliance between the human and non-human world.